2019
DOI: 10.1016/j.jhepr.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between non-alcoholic fatty liver disease screening guidelines in children and adolescents

Abstract: Prevalence of suspected NAFLD in overweight and obese children determined by two different NAFLD guidelines.Using the combination of elevated ALT and fatty infiltration on ultrasound (European guidelines) increases the detection rate of suspected NAFLD in at risk children. Highlights • Non-alcoholic fatty liver disease might be missed in at-risk children by relying on ALT values alone. • A significant percentage of obese children with fatty infiltration on ultrasound have low ALT values. • Children with fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…However, in a very recent study, two screening strategies were compared: the NASPGHAN strategy using an ALT cut-off of >2x the gender-specific upper limit of normal and the ESPGHAN strategy using elevated ALT >45 IU/L and/or fatty liver on ultrasound. The study showed that by relying on ALT values alone to screen for NAFLD, suspected NAFLD might be missed in many children who are at risk to develop the disease (49). In our study, it is possible that some subjects with US-diagnosis of NAFLD (due to low sensitivity) were enrolled in the control groups.…”
Section: Discussionmentioning
confidence: 95%
“…However, in a very recent study, two screening strategies were compared: the NASPGHAN strategy using an ALT cut-off of >2x the gender-specific upper limit of normal and the ESPGHAN strategy using elevated ALT >45 IU/L and/or fatty liver on ultrasound. The study showed that by relying on ALT values alone to screen for NAFLD, suspected NAFLD might be missed in many children who are at risk to develop the disease (49). In our study, it is possible that some subjects with US-diagnosis of NAFLD (due to low sensitivity) were enrolled in the control groups.…”
Section: Discussionmentioning
confidence: 95%
“…The European Society of Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) suggested that all overweight and obese children above 3 years old should be screened for NAFLD by performing abdominal ultrasound and liver function tests. Ezaizi et al suggested using a combination of elevated ALT and fatty infiltration on ultrasound to increase the detection rate and to avoid missed detection of suspected NAFLD children at risk ( 81 ). Ultrasonography is a safe and reliable tool for the diagnosis of NAFLD.…”
Section: Pediatric Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…Eligible studies were RCTs written in English assessing the effects of diet or physical activity on children with NAFLD, aged below or equal to 18-years old. As NAFLD diagnosis might be missed in children when relying only on alanine aminotransferase (ALT) [23], the present systematic review strictly evaluated RCTs in which NAFLD diagnosis was based either on imaging or biopsy. Imaging included ultrasound (US) or proton magnetic resonance spectroscopy ( 1 H-MRS) or magnetic resonance imaging (MRI) of the liver.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%